Kasugamycin influence on bacterial blight of coffee and on green coffee beans physicochemical quality - Barbosa, Ronei Aparecido; Santini, Paula Tristão; Guilherme, Luiz Roberto Guimarães (Coffee Science - ISSN 1984-3909, 2018)
Brazil stands out as the world’s largest coffee exporter. However, in the cold and windy regions, such as the southern of Minas Gerais, have been undergoing attack of diseases, including the bacterial blight of coffee caused by the bacterium Pseudomonas syringae pv. garcae, which despite not having the same importance as the coffee leaf rust, is causing damages and losses to the coffee plantation. The control is mainly done through preventive measures such as installation of windbreaks. When bacterial blight of coffee is already installed, the chemical control is used with syrups of copper-based products and antibiotics. The aim of the present study was to verify the efficiency of the antibiotic kasugamycin associated with copper hydroxide in the control of bacterial blight of coffee and raw coffee beans quality. The experimental design was a randomized block with five treatments, four replicates and plots of 10 plants in the field where the treatments consisted of different concentrations of the kasugamycin: 0.0, 250, 500, 750 and 1000 mL ha-1 added with 1.0 L copper hydroxide. The percent analysis was performed on the raw beans in order to verify their physical and chemical quality. The obtained results demonstrate that the solution is efficient in the control of bacterial blight of coffee as well as in the improvement of vegetative vigor and production, but does not influence the quality of raw coffee bean.